Combined Raman Spectroscopy and Digital Holographic Microscopy for Sperm Cell Quality Analysis - A. De Angelis; S. Managò; M. A. Ferrara; M. Napolitano; G. Coppola; A. C. De Luca (Journal of Spectroscopy)
The diagnosis of male infertility is vastly complex. To date, morphology, motility, and concentration have been used as key parameters to establish the sperm normality and achieve pregnancy both in natural and in assisted fecundation. However, spermatozoa from infertile men could present a variety of alterations, such as DNA fragmentation, alterations of chromatin structure, and aneuploidy, which have been demonstrated to decrease reproductive capacity of men. Therefore, the ability to see detailed relationships between morphology and physiology in selected spermatozoa with submicrometric resolution in a nondestructive and noninvasive way and within a functional correlated context could be extremely important for the intracytoplasmic sperm injection procedure. In this review, we describe label-free optical spectroscopy and imaging techniques, based on the combination of Raman spectroscopy/imaging with holographic imaging, which are able to noninvasively measure the (bio)chemistry and morphology of sperm cells. We discuss the benefits and limitation of the proposed photonic techniques, with particular emphasis on applications in detection/characterization of sperm cell morphological defects and photodamage, and the identification/sorting of X- and Y-bearing bovine spermatozoa.